2020
DOI: 10.21203/rs.3.rs-48557/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Diagnostic value of bronchoalveolar lavage-fluid soluble triggering receptor expressed on myeloid cells-1 (sTREM-1) concentration for neonatal ventilator-associated pneumonia

Abstract: Background: Soluble triggering receptor expressed on myeloid cells-1 (sTREM-1) has regarded as a biological marker of infection. We aimed to evaluate the diagnostic value of bronchoalveolar lavage (BAL)-sTREM-1 concentration in neonatal ventilator-associated pneumonia (NVAP). Methods: In this multicenter, controlled clinical trial of 60 preterm and 33 full-term neonates on mechanical ventilators, we measured concentrations of BAL-fluid and serum sTREM-1, serum C-reactive protein, and serum procalcitonin, as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…A recent study conducted by Zhou and his colleagues [17] reported that sTERM in the bronchoalveolar lavage-uid had sensitivity and speci city of 100% and 93.7% respectively with AUC of 0.938 in predicting VAP in neonates regardless of extrapulmonary infections. Moreover, Zhao et al [18] found that serum sTERM level showed a signi cant increase in the VAP group compared to the non-VAP one at 72 and 120 hours after ventilation.…”
Section: Discussionmentioning
confidence: 98%
“…A recent study conducted by Zhou and his colleagues [17] reported that sTERM in the bronchoalveolar lavage-uid had sensitivity and speci city of 100% and 93.7% respectively with AUC of 0.938 in predicting VAP in neonates regardless of extrapulmonary infections. Moreover, Zhao et al [18] found that serum sTERM level showed a signi cant increase in the VAP group compared to the non-VAP one at 72 and 120 hours after ventilation.…”
Section: Discussionmentioning
confidence: 98%
“…It also had a significant negative correlation with the leucocytic count in the ETT aspirate, total leucocytic count, and I/T ratio. A recent study conducted by Zhou et al reported that sTREM in the bronchoalveolar lavage‐fluid had sensitivity and specificity of 100% and 93.7%, respectively, with an AUC of 0.938 in predicting VAP in neonates regardless of extrapulmonary infections 22 . Moreover, Zhao et al found that serum sTREM levels showed a significant increase in the VAP group compared to the non‐VAP one at 72 and 120 h after ventilation 23 …”
Section: Discussionmentioning
confidence: 99%